More than just needles: An evidence-informed approach to enhancing harm reduction supply distribution in British Columbia - Mak Sunny; Preston Emma C; Buxton Jane A; Harvard Stephanie; Barley Jenny (BMC, 2008)
Abstract Background The BC Harm Reduction Strategies and Services (HRSS) policy states that each health authority (HA) and their community partners will provide a full range of harm reduction (HR) services to their jurisdictions and these HR products should be available to all who need them regardless of where they live and choice of drug. Preliminary analysis revealed wide variations between and within HAs. Methods The objective of this study is to analyze distribution of HR products by site using Geographic Information Systems (GIS) and to investigate the range, adequacy and methods of HR product distribution using qualitative interviews. The BC Centre for Disease Control pharmacy database tracks HR supplies distributed to health units and community agencies. Additionally, eleven face-to-face interviews were conducted in eight mainland BC communities using an open-ended questionnaire. Results There is evidence in BC that HR supplies are not equally available throughout the province. There are variations within jurisdictions in how HR supplies are distributed, adequacy of current HR products, collection of used needles, alternative uses of supplies and community attitudes towards HR. GIS illustrates where HR supplies are ordered but with secondary distribution, true reach and availability of supplies cannot be determined. Conclusion Currently, a consultant is employed to develop a 'best practice' document; relevant health files, standard training and protocols within HAs are also being developed. There is a need to enhance the profile and availability of culturally appropriate HR services for Aboriginal populations. Distribution of crackpipe mouthpieces is being investigated.